PENGEMBANGAN MEDIA FLIPBOOK MATERI PERUBAHAN CUACA DI KELAS III SEKOLAH DASAR - Shafa Shafarisna Farihah; Devi Firdayanti; Lintang Putri Ansani; Reris Sanabila (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
Abstract Age develops over time, so it is necessary to have an alignment and the use of developing information technology, especially in the field of education. Therefore, this study aims to produce a learning media regarding weather change material in grade III Elementary School. This research was carried out using the Research and Development (R&D) method which had been developed by Sugiyono. The research subjects in this scientific article involve several media experts, material experts to elementary school students. The results of this study are 1) learning media in the form of a flipbook of weather change material for grade III Elementary School, which includes audio-visual media and audio podcasts; 2) The quality of media products that have been made according to the assessment of several subjects ranging from media experts, material experts, to students are included in the appropriate category with details: 1) the material expert test got 84% results; 2) media expert test got 70.86% result or feasible; 3) small-scale test by students obtained 66.67% results or feasible; 4) the large-scale test by students obtained 74.71% or feasible results. Based on the media feasibility test results by the research subjects involved, it can be concluded that the flipbook learning media for weather change material is feasible to be used as a learning medium in class III Elementary School.